Scaling Nurturing Care Interventions in the Health Sector: A Theory of Change Perspective - Rasheed, Muneera A. (Frontiers in Public Health, 2022)
Nurturing care interventions postulated on strengthening caregiver-child relationships have proven to be effective for improving early childhood development outcomes in low and middle-income countries. Hence, scale-up of the interventions has been recommended with an emphasis on the health sector given the contact with families in the critical first 3 years of life. However, effective scale-up of an integrated intervention through the healthcare requires a theory of change approach elucidating pathways of sustainable change. In this viewpoint, I reflect on my experience of scaling the intervention in a private paediatric care setting. I realized buy-in from the health sector required realization of benefits to include health outcomes framed as the potential to improve quality of life and process of recovery; sustainable behaviour change required a culture that promoted Nurturing Care highlighting the role of leadership; subsequently improving the experience of frontline staff and at an individual level, this could be achieved through provision of supportive supervision-rooted in a framework of compassion. Lessons learned are shared to be considered for future integration efforts.